Parametric Evaluation of Responses on Single Degree of Freedom System - Saha, S; Mondal, M; Bhanja, S; Dey, T. K (International Journal of Computer Sciences and Engineering, 2025)
Structures must be designed to resist a variety of loads. Some of the loads are static (e.g., gravity and snow loads) while others are dynamic (e.g., wind and earthquake loads). Every structure is a complex system. So during dynamic analysis initially simplify this structure into single degree of freedom system. The present research work will be focused on parametric study of single degree of freedom systems with theoretical validation based on the principles of structural dynamics. Generally responses are easy to determine for periodic forcing function but are quite complicated and cumbersome if the forcing function become arbitrary. In such case numerical integration techniques are adopted. Duhamel integral method finds very useful application in this regard. The present work will be directed in determining the response of a single degree of freedom system under different types of arbitrary forcing functions. Models representing single degree of freedom systems with known characteristic and specifications will be tested using the shake table. Different periodic and aperiodic forcing functions will be fed into the controller and the response of the model to such excitation will be noted and plotted using the software available with the shake table. The theoretical responses will be developed using Duhamel integral method for aperiodic vibration. Comparisons of these results will be performed to validate the experimental work.